Poetic Style and Poetic Sources in the Anglo-Saxon Chronicle Common Stock Annals - Anlezark, Daniel (SELIM. Journal of the Spanish Society for Medieval English Language and Literature, 2024)
This article explores the evidence for the use of Old English poetry as a source in the annals of the common stock of the Anglo-Saxon Chronicle (to c. 892). The possibility that the compilers of the Chronicle either directly or indirectly derived information from vernacular poetry for entries of the late fifth and early sixth centuries was first raised by Henry Sweet. This essay reviews Sweet’s argument and widens the exploration of the annals, including the Cynewulf and Cyneheard episode in annal 757, for features such as alliteration and poetic vocabulary, suggestive of poetic sources and style.